2006
DOI: 10.1007/s11205-006-9029-7
|View full text |Cite
|
Sign up to set email alerts
|

An Introduction to ‘Benefit of the Doubt’ Composite Indicators

Abstract: composite indicators, data envelopment analysis, performance benchmarking, technology,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
384
0
16

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 565 publications
(400 citation statements)
references
References 32 publications
(26 reference statements)
0
384
0
16
Order By: Relevance
“…for output-specific inputs k we can have ( P m x,t ) k = ( P m x,t ) k when m = m . 10 Following our reasoning of the previous section, we can evaluate our shadow profit efficiency criterion by the following efficiency measure, which endogenizes the (shadow) price selection in the efficiency evaluation process:…”
Section: Shadow Prices and Dualitymentioning
confidence: 99%
“…for output-specific inputs k we can have ( P m x,t ) k = ( P m x,t ) k when m = m . 10 Following our reasoning of the previous section, we can evaluate our shadow profit efficiency criterion by the following efficiency measure, which endogenizes the (shadow) price selection in the efficiency evaluation process:…”
Section: Shadow Prices and Dualitymentioning
confidence: 99%
“…This method was originally proposed to evaluate macroeconomic performance. Elaboration of this method as a weighting method can be found in work of Cherchye et al [3]. A well-known property of the original DEA model [2] is units invariance; i.e.…”
Section: Composite Indicatorsmentioning
confidence: 99%
“…the CI values are independent of the units in which the constituent sub-indicator values are measured [4]. The DEA was already applied in the field of CI providing alternative weighting systems ( [11], [8], [3], [4], [22]). It was reported that the use of DEA overcomes some key limitations, the undesirable dependence of final results from the preliminary normalization of sub-indicators, and from subjectivity in weighting [4].…”
Section: Composite Indicatorsmentioning
confidence: 99%
See 2 more Smart Citations